MEDICATION ADHERENCE AND UNREPORTED DRUG USE DURING WORKUP FOR PRIMARY ALDOSTERONISM. (June 2018) - Sandbaumhüter, F.; Vogt, B.; Haschke, M.; Bohlender, J.
Abstract : Objective: Non-adherence to prescribed medication and unreported use of incompatible drugs may lead to misinterpretations of aldosterone-to-renin ratios during workup for primary aldosteronism but data are lacking. We compared antihypertensive drug prescriptions with measured plasma drug concentrations in patients with difficult-to-treat hypertension evaluated for possible aldosteronism. Design and method: Newly referred patients to our clinic with uncontrolled blood pressure despite 2 or more antihypertensives were prospectively recruited over 12 months. On the 1st visit, incompatible renin-angiotensin system inhibitors, beta-blockers, diuretics and central acting agents were routinely stopped before aldosterone-to-renin ratio determinations on a subsequent 2nd visit. Ca-antagonists and doxazosin were allowed. Patients with severe comorbidity or incompatible but mandatory drugs were excluded. Plasma concentrations of 10 prescribed antihypertensives (8 incompatible) out of 18 used were systematically determined on both visits by LC-MS/MS. Results were additionally compared with expected therapeutic concentration ranges. Results: Twenty-four patients were included: 42% female, age 54 ± 13 years, all with standardized glomerular filtration rate > 60. Mean interval between visits was 15 ± 6 days and average numbers of prescribed antihypertensives 3.2 ± 1.1 on the 1st vs. 1.1 ± 0.7 on the 2nd. In total, 76% of all antihypertensive prescriptions (60/79) were checked for presence in plasma on the 1st visit and 77% on the 2nd visit (20/26). On the 1st visit, 33% of patients showed discrepancies between prescriptions and plasma results (21% non-adherence/13% unprescribed drug use), 25% on the 2nd visit (0%/25%) and 46% for both visits combined (21%/29%). Unreported incompatible drugs were detected in 21% on the 2nd visit. For 1st and 2nd visits, 59% vs. 78% of plasma drug levels were within ± 50% of expected peak, 57% vs. 35% between peak and trough, and 17% vs. 15% below trough levels. Non-adherence because of previous day drug intake was thus suspected by quantitative analysis in additional 4 vs. 3 patients (17% vs. 13%). Conclusions: Unreported drug use is frequent during clinical work-up for primary aldosteronism and laboratory results need cautious interpretations in view of possible medication bias. Quantitative analysis of plasma drug concentrations may increase the sensitivity of non-adherence screening.